2022
DOI: 10.3390/healthcare10071198
|View full text |Cite
|
Sign up to set email alerts
|

The KIDSCREEN-27 Quality of Life Measure for Romanian Children Aged 6: Reliability and Validity of the Romanian Version

Abstract: The KIDSCREEN-27 represents a standardized, worldwide instrument, employed to assess the health-related quality of life in children. The purpose of the present study is to validate the KIDSCREEN-27 questionnaire for 6-year-old preparatory school children and verify its reliability, as well as to perform a comparison regarding the quality of children’s lives living in two cities in Romania: Arad, a provincial city, versus the second most developed city in the country, Cluj-Napoca. A total of 256 children of 6 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Specifically, the KIDSCREEN-10 Index has shown a Cronbach's α of 0.82, ICC of 0.70, and good validity [4,39]. The KIDSCREEN-10 Index maintained a good reliability (α of 0.81) even amidst the COVID 19-related study [29,40]. The SCARED has demonstrated a Cronbach's α of 0.74-0.93, ICC of 0.70-0.90, and good validity [41,42].…”
Section: Methodsmentioning
confidence: 94%
“…Specifically, the KIDSCREEN-10 Index has shown a Cronbach's α of 0.82, ICC of 0.70, and good validity [4,39]. The KIDSCREEN-10 Index maintained a good reliability (α of 0.81) even amidst the COVID 19-related study [29,40]. The SCARED has demonstrated a Cronbach's α of 0.74-0.93, ICC of 0.70-0.90, and good validity [41,42].…”
Section: Methodsmentioning
confidence: 94%
“…Its results are generally easy to understand and immediately suggest areas for intervention [35]. Other Romanian-validated instruments that can be further used for assessing quality of life are the SF-36 (short-form health survey) [36], the EQ-5D-3L (EuroQOL-five dimensions, three levels), the 5L, 5D instrument [37,38], and KIDSCREEN-27 [39], which have been applied in several studies. In our review, we found 20 studies in Romania assessing distress, mental well-being, fear of progression, coping, irrational beliefs, and emotion thermometers [40][41][42][43].…”
Section: Psychological Toolsmentioning
confidence: 99%
“…It is known that all sports activities improve the physical level and mental health, but at the same time they also have an impact on social ties, relationships and social attitude (Cszupich, 2020(Cszupich, , p. 2875. General well-being is adapted to the interaction of physiological, psychological and social factors that have a cause-and-effect relationship on health (Ardelean et al, 2022). Motivation has an important role, the intrinsic one being based on the individual's desire to engage in activities that rely upon the satisfaction of basic needs (Wikman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%